A bi-functional illusion device based on transformation optics. (21st February 2019) - Madni, Hamza Ahmad; Zheng, Bin; Akhtar, Maliha; Jaleel, Farrukh; Liu, Shuo; Mahboob, Athar; Iqbal, Shahid; Jiang, Wei Xiang; Cui, Tie Jun
Abstract: An illusion device based on a shifting-distance concept has been investigated using a linear coordinate transformation method. Distinguishing it from previously designed illusion devices, we construct a shift-illusion device featuring resizing and rotating for both active and passive scatterers, in case the shifting region and physical space shared the same origin point. Similarly, when the shifting region is foreign to the designed device, the proposed illusion design performs as a rotation and relocation-shifting device to change the location of the scatterer. In addition, these proposed devices behave like the stealth effect in the absence of any scatterer as the outer-boundary field distribution is not disturbed. Meanwhile, the proposed concept is further extended for different mapping styles to validate the shifting-illusion concept. The constitutive parameters of the proposed devices are homogeneous, which makes them more appreciable for real implementation. It is expected that the proposed design will find potential applications in illusion devices, such as object protection, camouflage, etc.